Interstellar scattering - New diagnostics of pulsars and the ISM - Macquart, Jean-Pierre (International Astronomical Union, 2013)
Extreme Scattering Events and pulsar secondary spectra have highlighted fundamental problems in our understanding of the dynamics of interstellar turbulence. We describe some of these problems in detail and present the theory behind the technique of speckle imaging, which offers a prospect of revealing fundamental properties of the turbulence. It also offers the prospect of resolving pulsar magnetospheres on ~ 10 nas scales.